Assessment of Antenatal Care Services Utilization and Its Associated Factors - Paudel, Nabaraj; Paneru, Damaru Prasad; Pahari, Sandip; Poudel, Arati; Sharma, Yam Prasad (Journal of Nepal Health Research Council, 2024)
Background: Every pregnant woman supposed to have Antenatal care visits at least four times during 4th, 6th, 8th and 9th month of gestation. This contributes to the reduction in maternal mortality. The main objective of the study was to assess the utilization of antenatal care services and its associated factors in Pokhara Metropolitan.Methods: A community based cross-sectional analytical study was conducted in Pokhara Metropolitan between 16th May 2019 to 30th June 2019 among 325 mothers using probability proportional to size sampling and face to face interview. Ethical approval was obtained from Nepal Health Research Council. Data analysis was done using SPSS version 22 and Chi-square test and binary logistic regression analysis was performed. Results: A total of 97.2 percent mothers had at least one time visit for ANC checkup while 88.6 percent mothers received four ANC visits as per protocol. A total of 94.6 percent mothers got counseling on early detection and management of complications, 95.9 percent consumed iron and folic acid and 94.3 percent consumed de-worming tablets. Mothers health literacy mobile phone ownership (AOR=11.26, 95% CI: 9.70-13.03), husband’s attitude towards ANC (AOR=6.71, 95%CI: 1.60-28.10), awareness on pregnancy complications (AOR=4.62, 95% CI: 2.53-21.73), and which isdecision making on household expenditure by self (AOR 8.57%, 95% CI: 3.64-9.48) history of abortion (AOR=5.22, 95%CI: 1.71-15.30) were the factors associated with ANC service utilization. Conclusions: Majority of the pregnant women were found to be utilizing ANC services. Mobile phone ownership, health literacy, husband's attitude towards ANC, decision making on household expenses, awareness on pregnancy complications and history of abortion were the significant factors associated with ANC service utilization.Keywords: Antenatal care; factors associated; Pokhara; utilization.